2014
DOI: 10.1093/rheumatology/keu385
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of fatal rapidly progressive interstitial lung disease associated with juvenile dermatomyositis

Abstract: High serum levels of IL-18, KL-6, ferritin and anti-MDA5 antibodies (e.g. >200 units by ELISA) are associated with RP-ILD. These can be used as an indication for early intensive treatment. Both alveolar macrophages and autoimmunity to MDA5 are possibly involved in the development of RP-ILD associated with JDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 40 publications
4
103
0
Order By: Relevance
“…Interstitial lung disease was more common in both cohorts with this autoantibody, compared to patients without these antibodies. In the UK patients, other common features included oral and cutaneous ulceration, arthritis and milder muscle disease, which was similar to findings in US and European adult cohorts with MDA 5 autoantibodies .…”
Section: Serologic Classification Of Jiimssupporting
confidence: 84%
“…Interstitial lung disease was more common in both cohorts with this autoantibody, compared to patients without these antibodies. In the UK patients, other common features included oral and cutaneous ulceration, arthritis and milder muscle disease, which was similar to findings in US and European adult cohorts with MDA 5 autoantibodies .…”
Section: Serologic Classification Of Jiimssupporting
confidence: 84%
“…Fulminant presentations with ILD, CADM and anti-MDA-5 autoantibodies may be especially frequent in Japanese patients compared with other east Asian or non-Asian patients [35,64], although a publication bias cannot be excluded. In a Japanese retrospective series of 54 patients with JDM [66], 10 had rapidly progressive ILD and 19 had chronic ILD, illustrating the particularly frequent pulmonary involvement in the Asian population.…”
Section: Rapidly Progressive Ildmentioning
confidence: 99%
“…Specificity for anti–NXP‐2 or anti‐MDA5 autoantibodies, visualized as a 140‐kd band, was determined by enzyme‐linked immunosorbent assay, as described previously . Since recent studies in the literature have identified important associations between the clinical features of juvenile DM and the presence of MSAs , and relatively fewer patients with myositis‐associated autoantibodies (MAAs) were present in the biopsy cohort (with low numbers in individual groups), we elected to focus on the patient groups in whom the frequencies of MSAs, i.e., anti–TIF‐1γ, anti–NXP‐2, anti‐MDA5, and anti–Mi‐2, were sufficient for these analyses. Patients with MAAs or unidentified bands were excluded during the statistical analyses of associations with muscle biopsy scores and associations between muscle biopsy scores, MSA subtypes, and long‐term outcomes.…”
Section: Methodsmentioning
confidence: 99%